SIRT3 Regulation of Mitochondrial Quality Control in Neurodegenerative Diseases - Meng, Hao; Yan, Wan-Yu; Lei, Yu-Hong; Wan, Zheng; Hou, Ye-Ye; Sun, Lian-Kun; Zhou, Jue-Pu (Frontiers in Aging Neuroscience, 2019)
Neurodegenerative diseases are disorders that are characterized by a progressive decline of motor and/or cognitive functions caused by the selective degeneration and loss of neurons within the central nervous system. The most common neurodegenerative diseases are Alzheimer’s disease (AD), Parkinson’s disease (PD), and Huntington’s disease (HD). Neurons have high energy demands, and dysregulation of mitochondrial quality and function is an important cause of neuronal degeneration. Mitochondrial quality control plays an important role in maintaining mitochondrial integrity and ensuring normal mitochondrial function; thus, defects in mitochondrial quality control are also significant causes of neurodegenerative diseases. The mitochondrial deacetylase SIRT3 has been found to have a large effect on mitochondrial function. Recent studies have also shown that SIRT3 has a role in mitochondrial quality control, including in the refolding or degradation of misfolded/unfolded proteins, mitochondrial dynamics, mitophagy, and mitochondrial biogenesis, all of which are affected in neurodegenerative diseases.